THE HEADACHE ASSOCIATED WITH SEXUAL ACTIVITY: A CASE REPORT AND LITERATURE REVIEW - Y. E. Azimova; A. Z. Vinarov; G. R. Tabeeva (Сеченовский вестник)
Primary headache associated with sexual activity (PHASA) is a form of primary headaches, precipitated by sexual activity, in the absence of any intracranial disorder. Two types of PHASA are discerned: preorgasmic and orgasmic. A case of 44 years old patient with orgasmic headache is presented. Principles of differential diagnosis of orgasmic headache with secondary headaches and management of patients with PHASA are discussed.